Class, Education and Mindset - Allan, David (PRISM: Casting New Light on Learning, Theory and Practice, 2018)
In this think piece, I discuss the implications of class in relation to mindset and educational opportunities. I wish to illustrate how attitudes – particularly those influenced by social positionality – can be a significant contributor to education, employment, and social status. This interest stems from my previous research in educational disaffection and student marginalisation.